Guidelines for robotic credentialling in reconstructive and functional urology. Consensus study - Frances Harley; Rasa Ruseckaite; Eva Fong; Henry Han‐I Yao; Hashim Hashim; Helen E. O'Connell (BJUI Compass)
Abstract Objectives This study aims to define criteria for robotic reconstructive and functional urology credentialing using expert consensus. A recent narrative review identified a lack of standardised minimal requirements for performing robotic‐assisted surgery procedures. The substantial variability or absence of a standardised curriculum and credentialing process within a highly specialised surgical field is often insufficient to guarantee surgeon proficiency and could potentially jeopardise patient safety. Subjects and Methods Thirty‐five international robotic surgery experts in urology and urogynaecology, selected based on surgical and research expertise, were invited to participate as expert panellists. Using a modified Delphi process the experts were asked to indicate their agreement with the proposed list of recommendations that was identified from the literature and review of relevant international credentialing policies in three electronic survey rounds. Results Fourteen experts participated in round 1 of online surveys, 9 in round 2 and 13 in round 3. From 50 statements presented to the Delphi panel in round 1, a total of 39 recommendations (32 from round 1, 4 from round 2 and 3 from round 3) with median importance (MI) ≥ 7 and disagreement index (DI) < 1 were proposed for inclusion into the final draft set and were reviewed by the project team. Panellists agreed reconstructive and functional urology required its own specific modular training curriculum as the foundation for robotic training and a surgeon must have appropriate training i.e., fellowship or evidence of speciality training in functional urology. Conclusions This was the first study to develop preliminary guidelines on credentialing for robotic surgery in reconstructive and functional urology. A Delphi approach was employed to establish comprehensive credentialing criteria for robotic‐assisted surgery. The consistent adoption of these criteria across institutions will foster the proficiency of robotic surgeons and has the potential to bring improvements in patient outcomes.